2004
DOI: 10.1128/jcm.42.9.4349-4354.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Avian H3N3 and H1N1 Influenza A Viruses Isolated from Pigs in Canada

Abstract: H3N3 and H1N1 influenza A viruses were isolated from Canadian pigs in 2001 and 2002. These viruses are phylogenetically related to waterfowl viruses and antigenically distinct from reference swine influenza viruses. The isolation of these viruses reemphasizes the potential for interspecies transmission of influenza viruses from waterfowl to pigs in North America

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 65 publications
2
82
1
2
Order By: Relevance
“…In other studies, most of the viral proteins have been shown to have some influence on host range. 16,58,77,97,104 …”
Section: Polymerases and Other Viral Proteinsmentioning
confidence: 99%
“…In other studies, most of the viral proteins have been shown to have some influence on host range. 16,58,77,97,104 …”
Section: Polymerases and Other Viral Proteinsmentioning
confidence: 99%
“…8 The increasing antigenic diversity in influenza subtypes circulating in swineherds has generated concern among swine veterinarians regarding the ability to detect antibodies generated against the varied influenza viruses. 3,[5][6][7][8][9]14,24 In addition, characterization of antibody profiles provides important information on the ability of vaccines to stimulate a protective immune response against disease as genetically different viruses within and across subtypes continue to emerge and infect swine herds. The constant ongoing genetic changes in influenza viruses have reduced the ability of practitioners to accurately diagnose and develop effective vaccination strategies (Kitikoon P, Thacker BJ, Vandertop R, et al : 2002, The immune response to vaccination and challenge with H3N2 influenza virus.…”
Section: Introductionmentioning
confidence: 99%
“…LPAI viruses have been occasionally isolated from pigs in the field as shown in Table IV [17,23,24,26,40,43]. Though most of these viruses have an H1 or H3 HA, HA subtypes that are usually restricted to birds can also cross the species barrier to pigs.…”
Section: Swine As An Intermediate Host For the Transmission Of Avian mentioning
confidence: 99%